Experimental approach to investigate reinforced clay - Chegenizadeh, Amin (Curtin University, 2012)
Soil reinforcement with discrete flexible fibres has always been an issue for further research. In Geotechnical engineering field, the research on sandy soil has considerably been more than the clayey one. The main reason for this lack can be expressed as the complexity of clayey material due to their cohesion and interaction between clay and reinforcement.The present research aims to show possibility of discrete fibre usage in clay. For this purpose, selection of material has been conducted with special care to make the project outcome applicable to industry projects. The fibre which was used for this research prepared by BASF Company in Western Australia and currently is used in fibre reinforced concrete for infrastructure projects. Kaolin has been used as soil part and provided by Prestige Company.Experimental approach was applied to investigate the effect of different parameters on composite soil strength. These tests cover the variety range of soil mechanics tests from compaction tests to triaxial compression tests. The results from all the tests were presented in the thesis.A theoretical model was also developed for clayey material for the first time with the use of modified cam clay model to predict the behaviour of samples precisely. This model is based on the rule of mixture and considers the effect of soil and fibre separately. The model was validated with the results from CD triaxial test.